Hysteresis in phase volumes, compositions and interfacial roughness in model OPV-small-molecule/polymer thin-films - Anthony Higgins (Soft Matter, 2024)
Domain morphology and composition, and the structure of interfaces between domains are key factors in the performance and stability of organic photovoltaics (OPVs) fabricated from polymer/small-molecule blends. In this study, we investigate the evolution of composition, phase-volume and interfacial roughness in model polymer/small-molecule bilayers, in response to thermal annealing. Polystyrene/fullerene mixing is studied as a function of annealing temperature, using in-situ neutron reflectivity, in thin-film bilayer samples comprising pure component or mixed layers. Remarkably, we discover that thermal annealing at temperatures around or above the reported glass transition temperatures, Tg, of the components can result in extensive mass-transfer between layers, that has the superficial appearance of equilibration, but leaves the layer compositions, thicknesses, and/or the interfacial composition profile in a non-equilibrium state. This is not merely a case of slow kinetics near Tg, as subsequent heating to higher temperatures, followed by cooling, reveals pronounced hysteresis in these systems. This has important implications for the measurement of equilibrium compositions in polymer/small-molecule mixtures for OPV applications, and for device stability during operation.